Rise up: Okinawa protests against foreign occupation - Dietrich, John Edwin, III (Kansas State University, 2016)
Okinawa, Japan has a long history of struggle with Japan and the United States of America. Okinawa was annexed by the Japanese during the Shogunate, mistreated by Imperial Japan during World War II, destroyed during the Battle of Okinawa, and occupied by U.S. military. Okinawa hosts some of the largest U.S. military bases outside of the Continental United States. Since Okinawa has been occupied by the U.S. military since World War II, it also has a history of contentious politics and protests against the occupation. Okinawa’s economy and cultural identity within the domestic and international spheres with the U.S. military and the Government of Japan has shaped its political protest identities. The “Okinawan Struggle” has evolved and into a new form, but often seen as a long lasting and unified struggle. This thesis explores Okinawa’s different protest episodes during different governing administrations and different economic structures.
Keywords: Military Occupation; Okinawa; Protest; Social Movement